ANALISIS ZAKAT PRODUKTIF DAN DAMPAKNYA TERHADAP PERKEMBANGAN USAHA MIKRO MUSTAHIK - Mastura . (FEBI IAIN Langsa, 2017)
This research aims to find out the influence of zakat on Mustahik’s micro business development. The sample of this research is zakat, the educational employees in 2013 followed by 46 samples of micro businesses. This was quantitative research using multiple linear regression analysis technique, supported by a model test and statistical tests using Eviews 7 version program assistance. The results of research which was conducted on alpha 5%, showed that the major variables including the zakat, the man power and education affect on profits. Partially, the influence of zakat towards income is positive and significant, in which the increase of zakat Rp 1 balanced to that of income for Rp 4. The increasing of zakat will raise capital, resulted in raising the production as well as the profits. The influence of laborer towards income is also positive and significant, thus the increasing number of laborer for 1 person will enlarge the income of Rp 2,174,221. The increasing number of laborer would raise the level of production and profits. The influence of education towards income is positive and significant; it stood at 1 compared to Rp 104,9202. This meant that the higher education the better production will be.